Design Concepts to Support Management of Outpatient Consultations in the Veterans Health Administration. (September 2016) - Militello, Laura; Diiulio, Julie; Russ, Alissa; Savoy, April; Flanagan, Mindy; Patel, Himalaya; Weiner, Michael; Roudebush, Richard L.
This poster describes a project to improve understanding of the challenges associated with managing consultations in the Veterans Health Administration (VHA). We conducted interviews and observations with primary care providers and specialists at two VHA facilities. Using qualitative analysis, we identified cognitive requirements, challenges associated with each, and design seeds. During the poster session, we will present design concepts exploring interventions to support management of consultations.